PENERAPAN METODE QUALITY FUNCTION DEPLOYMENT UNTUK PENGEMBANGAN DESAIN PRODUK - Santa Laetitia Putri; Agung Sutrisno; Charles Punuhsingon (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2020)
Design of quality product is a design that based on the basic functions of the product that are adjusted into quality and capacity, as well as added value that can attract the attention of consumers. Product design development is very important because in this era of economic global competitive, innovation is very important to achieving advanced in the global market. The most important thing from product design development is fulfillment of the needs and desires of consumers.This research uses the quality function deployment (qfd) method, which is a design method that can translate the needs and desires of consumers to technical specifications in fulfillment customer satisfaction. QFD method is the most preferred method for developing a product's design. The product in this research is a standard helmet. Nowdays, helmet become one of safety needs, because all motorcycle users must use helmets if they want to go anywhere. But not few riders who do not use a helmet when driving because of discomfort when using a helmet. For this reason, a multifunctional helmet is needed so that the rider can feel comfortable and safe when using the helmet. According to surveys and interviews, there are six important things conveyed by consumers for the development of this standard helmet, consist of: using a full face design, made from cold ingredients, use colors navy and silver, and added features of a microcontroller chip, wireless and password, microphone. As for the overall analysis with house of quality (HoQ) there are seven priority of technical specifications, namely: the shape design of standard helmet, flexibility of standard helmet in use, a multifunctional standard helmet, safety for helmet’s user, comfort for helmet’s user, the complete features, and attractive colors. Keywords : Product design development, QFD, HoQ